The Potency Of Glutamate Producing Lactic Acid Bacteria Isolated as Additive Feed In Improving Broiler Performance - Maslami, Vebera; Marlida, Yetti; Mirnawati, Mirnawati; Shafan Nur, Yuliaty Shafan (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
ABSTRACT Glutamate is one of the amino acids that can act as flavor neurotransmitter. Some lactic acid bacteria (LAB) are known as producers of glutamate. Such LAB could be widely found in many fermentation products. The objectives of this study were to isolate and characterize some glutamate producing LAB isolated from West Sumatera fermented food products (dadih, asam durian, ikan budu and tapai). A total of 1,014 LAB was isolated from the fermented food products. Of these, 40 isolates were considered the best based on their ability to produce inhibition zones >2mm in the presence of 2% CaCO3. Qualitative analysis using thin layer chromatography and quantitative analysis using spectrophotometer revealed that 27 of the 40 LAB isolates produce glutamate. The highest glutamate production was found in LAB of dadih origin (coded as N32). N32 produced a glutamate of 38.25 mg/ml. N32 was found to be gram positive, negative for catalase, oxidase and motility, and can utilize sugars in the form of lactose, glucose and mannitol. The N32 was identified to be Lactobacullus sp. Thus N32 (Lactobacullus sp) from dadih has the potential to produce glutamate acid. Keywords: glutamate, building blocks, lactic acid bacteria, food fermentatio